Implementation of the Multimedia Development Life Cycle (MDLC) in Solar System Application Design - Aryani, Diah; Noviandi, Noviandi; Siti Fatonah, Nenden; Akbar, Habibullah (International Journal of Science, Technology & Management, 2024)
Augmented Reality (AR) technology has had an impact on changes in the world of education, especially improving the quality of education which has positively influenced the learning and teaching process, with the use of tools in education it has proven effective in improving the learning and teaching environment in the classroom and even changing the way we view education. This research aims to design a solar system application as an alternative AR-based learning media by integrating 3D models, animation and video to improve the learning experience of students, especially students of SDN Larangan 5 Tangerang. This is based on the lack of student learning experience, especially regarding the solar system material which is still lacking and not yet varied because so far SDN Larangan 5 has not used technology, especially AR technology in the learning process and still uses book texts and videos. This research used the Multimedia Development Life Cycle (MDLC) method and usability testing was carried out using the System Usability Scale (SUS) method with a total of 33 respondents with a test result of 78 which indicates the level of user satisfaction with the solar system application that has been tested on the respondents.